Difficulties in the pronunciation of english vowels by the fifth-year students from modern languages major at the Foreign Language Department of the University of El Salvador during the year 2015 - Díaz Rodríguez, Grabiela María
The present project is a research based on a problem affecting students from the Foreign Language Department. Firstly, it is a study to know in a deeper way what are the: Difficulties in the pronunciation of English vowels by the fifth-year students from Modern Languages major at the Foreign Language Department of the University of El Salvador during the year 2014. Secondly, Pronouncing English vowel sounds is one of the most challenging tasks for students. The experience with our native language affects our perception of nonnative speech sounds in a systematic, predictable manner. English uses the same writing system as Spanish a,e,i,o,u but instead of having a one-to-one correspondence between grapheme and pronunciation, the five written vowels, in combination or alone, represent twelve phonemes in stressed syllables /i, ɪ , e, ɛ , æ, a, ɔ , ʌ , o, ʊ , u, ə /. This study pretends to analyze those phonetic difficulties when pronouncing English pair of vowels for example: /i-ɪ / feel-fill, /e-ɛ / chase-chess, /ʊ -u/ full-fool, / a- ɛ / bar-bear, / æ- ʌ /cap-cup, /ɛ - ʌ / bet-butt /o- ɔ / bowl-ball and / æ- a- ʌ / hat-hot-hut, trying to focus in those which are more difficult at the moment of pronouncing them correctly. In addition, this research will focus on the pronunciation of some long and short vowel sounds and the perception of the sound schwa /ə/. Thirdly, the methodology chosen to be applied in this study will allow the researchers to know the difficulties in the pronunciation of English vowels by students. Exploratory research is characterized by its flexibility in study development, which fits perfectly in this investigation since there is not another study previously established. Indeed, it offers the feasibility of generating a series of hypotheses or questions toward the problem. Also, while a mixed research is taking place, involving the mixing of quantitative and qualitative research methods, approaches, or other paradigm characteristics. A nonexperimental research will be done; the information will not be manipulated. Nonrandom sampling techniques will be used where purposive sampling is the one selected to be used in the research